2008
DOI: 10.1007/s10661-008-0324-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respirable dust exposures in an opencast coal mine

Abstract: All major opencast mining activities produce dust. The major operations that produce dust are drilling, blasting, loading, unloading, and transporting. Dust not only deteriorates the environmental air quality in and around the mining site but also creates serious health hazards. Therefore, assessment of dust levels that arise from various opencast mining operations is required to prevent and minimize the health risks. To achieve this objective, an opencast coal mining area was selected to generate site-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 8 publications
(8 reference statements)
1
28
0
Order By: Relevance
“…As expected, the increment was higher near the source and it decreased with increase of distance from source due to settling of coarse particles ( Fig. 8b) Onder and Yigit 2009). …”
Section: Pm Concentrationsupporting
confidence: 77%
See 2 more Smart Citations
“…As expected, the increment was higher near the source and it decreased with increase of distance from source due to settling of coarse particles ( Fig. 8b) Onder and Yigit 2009). …”
Section: Pm Concentrationsupporting
confidence: 77%
“…Earlier studies have also reported low fine particle concentration in mine atmosphere with PM 1-2.5 and PM 1 concentration varying in the range 4-6 μg m −3 and 6-8.5 μg m −3 . Mining activities predominantly generate coarser particles (Aneja et al, 2012;Onder and Yigit, 2009;Ghose and Majee, 2001). The fine particle concentration in mine atmosphere is therefore low.…”
Section: Pm Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the current study using propensity scoring serves as a validation of the previous observational studies documenting health disparities in mountaintop mining populations. These findings may be combined with additional studies conducted in Europe, Australia, and Asia that also find poor public health outcomes such as respiratory illness or cancer from exposure to surface coal mining activity (Temple & Sykes 1992;Yapici et al 2006;Onder & Yigit 2009;Figure 2. Boxplots for logit propensity: MTR mining and non-mining groups.…”
Section: Discussionmentioning
confidence: 97%
“…This rock material in normally found as an innate component of the coal, however, it is typically not a substantial foundation of silica [18]. According to the authors of [19] most major mining operations executed through the open cast mining method cause dust. Key activities that result in dust being produced include drilling, blasting, stacking, unstacking, and conveying of coal.…”
Section: Environmental Management Accountingmentioning
confidence: 99%